A demographic factor as a determinant of migration: what is the effect of sibship size on migration decisions?. (December 2019) - Zhao, Jianmei; Zhong, Hai
Abstract: Developing countries often lack an adequate social security system, and elderly parents rely heavily on their children for support. Aging populations and low-fertility rates are an emerging trend in developing countries. In this paper, we examine the effects of sibship size on individuals' internal migration decisions in China. We find that the number of siblings has a positive effect on individual migration decisions, but this effect is non-linear and marginally increasing. Second, we find that having brothers has a more significant effect on migration decisions than having sisters. Finally, although of different magnitudes, the effects are persistent across genders, Hukou status, and education levels.